2000
DOI: 10.1006/mthe.2000.0210
|View full text |Cite
|
Sign up to set email alerts
|

Liver Cirrhosis Is Reverted by Urokinase-Type Plasminogen Activator Gene Therapy

Abstract: Liver cirrhosis represents a worldwide health problem and is a major cause of mortality. Cirrhosis is the result of extensive hepatocyte death and fibrosis induced by chronic alcohol abuse and hepatitis B and C viruses. Successful gene therapy approaches to this disease may require both reversal of fibrosis and stimulation of hepatocyte growth. Urokinase-type plasminogen activator (uPA) may serve this function, as it is an initiator of the matrix proteolysis cascade and induces hepatocyte growth factor express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
86
1
8

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 21 publications
7
86
1
8
Order By: Relevance
“…Other substances have proven to be effective: vitamins C, E and C + E (24), losartan (28), gliotoxin (24), pirfenidone (29), relaxin (30), and Han-Dan-Gan-Lee (31) also reduced fibrosis in rat livers. Hepatic growth factor (22), halofuginone (32) and adenovirus with urokinase plasminogen activator (25) induced collagen reduction in cirrhosis models. It should be pointed out that treatment with pirfenidone reduced 40% of the fibrosis induced by CCl 4 (23).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Other substances have proven to be effective: vitamins C, E and C + E (24), losartan (28), gliotoxin (24), pirfenidone (29), relaxin (30), and Han-Dan-Gan-Lee (31) also reduced fibrosis in rat livers. Hepatic growth factor (22), halofuginone (32) and adenovirus with urokinase plasminogen activator (25) induced collagen reduction in cirrhosis models. It should be pointed out that treatment with pirfenidone reduced 40% of the fibrosis induced by CCl 4 (23).…”
Section: Discussionmentioning
confidence: 95%
“…The reduction of ALT (-17.6%) and AST (-12.2%) also points to a reduced hepatocellular necrosis, decreasing the cycles of cell death and fibrotic regeneration that are characteristic of the cirrhotic process. Other treatments also improved hepatic conditions in fibrosis and cirrhosis models with down-regulation of enzymes of hepatic function, such as gliotoxin (21), hepatic growth factor (22), pirfenidone (23), vitamins C and E (24), urokinase plasminogen activator (25), and partial hepatectomy (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 However, none of those strategies has been examined for an antiviral effect on HCV. We found that the AxCA-rIFN vector inhibited HCV replication in vitro (unpublished data), and the anti-HCV effect may add an advantage to the IFN-a gene therapy for HCV-induced LC.…”
Section: Discussionmentioning
confidence: 99%
“…They are based on enhancing the degradation of extracellular matrix by overexpressing urokinase-type plasminogen activator (34) or matrix metalloproteinase 1 (35) or on stimulation of hepatocyte proliferation by expression of hepatocyte growth factor (36). The molecular decoys described here act by a novel mechanism of preventing excessive production of fibrillar collagens.…”
Section: Discussionmentioning
confidence: 99%